Modelling German Covered Bonds - Spangler, Manuela (Mathematische Optimierung und Wirtschaftsmathematik | Mathematical Optimization and Economathematics,, 2018)
Manuela Spangler deals with the default risk modelling of German covered bonds (Pfandbriefe). Existing credit risk models are not suitable for this purpose as they only consider the creditworthiness of the issuer while product-specific features are not taken into account. The author develops a multi-period simulation-based Pfandbrief model which adequately accounts for the product's most important characteristics and risks. The model provides a flexible framework for structural analyses and can be easily extended for tailor-made investigations. While the focus of the work is on the specification of the model itself, simulation results from an exemplary model calibration are also discussed. Content Pfandbrief Characteristics Credit Risk Models: A Literature Review The Pfandbrief Model Model Calibration and Scenario Generation Simulation Results Target Groups Scientists and students in the field of financial mathematics, quantitative finance and banking Practitioners in the field of risk management, rating agencies and regulators About the Author Manuela Spangler works as a quantitative risk analyst for a large asset management company and holds a PhD in mathematics from the University of Augsburg. Prior to her current position, she worked as a risk manager and financial engineer in the banking and insurance sector for various years.